Writing Workbook as Scaffolding Aid for Junior High School Students - Ima Melati Dewi (Universitas Negeri Malang, 2014)
This study was conducted to develop a writing workbook as a supplementary material for the eighth graders of SMPN 3 Jember. The result of the preliminary study showed that there was only small portion of writing activities in the existing textbook. As a result, students got many difficulties in writing skills. The research and development (R&D) procedure was employed in this study. The design used in developing the workbook was the adaptation model of development by Borg and Gall (1983). The procedures employed in this study were needs analysis, instructional goal, material de-velopment, expert validation, try-out, and final product. The information from teachers and students in needs analysis served as a basis for developing the materials. To evaluate the developed materials, expert validation by a material development expert and a subject matter expert was carried out. The information from the experts was used to improve the quality of the materials. After trying out the ma-terials, the teacher was given observation form and the students were given checklists to examine the acceptability and the utility of the product in the field. Based on the result of the data analysis, it can be concluded that the developed materials were categorized good and can be used as supplemen-tary writing materials for the eighth graders of SMPN 3 Jember. Key Words: developing, writing workbook, supplementary material, SMPN 3 Jember